Interventions for Medical Students’ Psychological Wellbeing: A Scoping Review (European Journal of Behavioral Sciences, 2025)
Amidst the acknowledged challenges to students' psychological wellbeing in medical education, this review aims to map and assess the wellbeing interventions employed in studies aimed to enhance medical students' quality of life and overall mental health and wellbeing. Despite the recognised need to address psychological wellbeing in medical education, ambiguity remains regarding the nature, range and effectiveness of the wellbeing interventions that have been made available to medical students for this purpose. Methods: Using the Arksey–O'Malley scoping review method, authors systematically searched Medline, PsycINFO, Embase, Cochrane, and Web of Science databases for publications from inception to December 2024. Two reviewers assessed study eligibility and extracted data on wellbeing interventions aimed at improving the psychological wellbeing of medical students. Results: Sixty papers met the criteria for inclusion as studies focusing on interventions targeting the psychological wellbeing of medical students. Our findings identified a diverse range of interventions, including mindfulness-based interventions, cognitive-behavioural therapy, mind-body medicine, pass/fail grading, curriculum changes, and wellness programs. These interventions demonstrated varying degrees of effectiveness in reducing poor psychological wellbeing and promoting positive outcomes. Specifically, mindfulness-based interventions showed positive impacts on anxiety reduction while cognitive-behavioural therapy interventions exhibited favourable effects on stress alleviation and psychological morbidity. Furthermore, students enrolled in pass/fail evaluation systems demonstrated substantial initial wellbeing improvement compared to other academic interventions. However, the effectiveness of mind-body medicine interventions, diverse curriculum changes, and wellness programs presented mixed results, stressing the need for tailored interventions. Despite the implementation of various interventions, uncertainty persists regarding their alignment with students' preferences, influenced by factors such as intervention format, time constraints, and academic pressures. Conclusions: The findings of this review offer insights into the nature, effectiveness and acceptability of psychological wellbeing interventions for medical students, underlining the need for interventions that align with students' preferences and choices. Continuous evaluations and adaptations of interventions are essential to meet evolving needs and to foster resilience among medical students.